ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT MENGIKUTI PELATIHAN BREVET PAJAK - Asrofi Langgeng Noerman Syah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research has purpose to investigate the public's interest in participating in tax brevet training at the Politeknik Harapan Bersama so that it can be seen what factors influence it. Public interest in this research was influenced by career motivation, quality motivation and knowledge motivation. Primary data sources used by distributing questionnaires and interviews. The population of this research was the general public who have participated in tax brevet since 2017 – 2020 with 106 participants at the Politeknik Harapan Bersama. The number of samples used based on the calculation of the Slovin formula were 51 respondents with the sampling method, namely random sampling. Analysis of the data in this study using multiple linear regression. The results showed that career motivation had an effect on people's interest in participating in tax brevet training at the Politeknik Harapan Bersama but quality and knowledge motivation had no effect on people's interest in participating in tax brevet training at the Politeknik Harapan Bersama.